PERAN PEMBELAJARAN KONTEKSTUAL DALAM MENDORONG DEEP LEARNING DAN PENGUATAN NILAI MODERAT DI SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - RIZKI KHOIRIANA; ISDARYANTI, BAROKAH; WIDIARTI, NUNI; AVRILIANDA, DECKY (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of contextual learning in promoting deep learning and strengthening moderate values among elementary school students using a Systematic Literature Review (SLR) approach. The study is motivated by the need to enhance students' character development in the context of social diversity, as well as the persistence of surface learning practices in primary education. Data were collected by reviewing relevant scientific articles from reputable databases using keywords such as "contextual learning," "deep learning," and "moderate values." From an initial search of 45 articles, 15 articles were selected based on inclusion and exclusion criteria. The findings indicate that contextual learning plays a significant role in encouraging deep learning by connecting learning materials with students' real-life experiences, fostering critical thinking, reflection, and meaningful understanding. Furthermore, contextual-based deep learning contributes to strengthening moderate values such as tolerance, respect for diversity, cooperation, and inclusiveness. The effectiveness of this approach is influenced by factors such as teacher competence, learning strategies, and classroom environment. However, challenges remain, including limited teacher understanding of deep learning concepts and constraints in learning resources. In conclusion, contextual learning integrated with deep learning is an effective strategy to enhance both cognitive and character development, particularly in strengthening moderate values among elementary school students.